BRCAness and Prognosis in Triple-Negative Breast Cancer Patients Treated with Neoadjuvant Chemotherapy. - Hirokazu Tanino (PLoS ONE, 2016)
BRCAness is defined as the set of traits in which BRCA1 dysfunction, arising from gene mutation, methylation or deletion, results in DNA repair deficiency. In the present study, we addressed BRCAness, therapeutic efficacy, recurrence, and survival in patients with triple negative breast cancer (TNBC) who were treated with neoadjuvant chemotherapy at Kitasato University Hospital, Japan, between April 2006 and October 2012. BRCAness was determined by preoperative core needle biopsy (CNB) specimens and surgical specimens. Assay was performed using Multiplex Ligation-dependent Probe Amplification (MLPA) with P376-B2 BRCA1ness probemix (MRC-Holland, Amsterdam, The Netherlands). The relative copy number ratio of each sample was compared to Human Genomic DNA (Promega, Madison, WI, USA) as reference samples was calculated with Coffalyser.NET default settings. The BRCAness score was calculated with the relative copy number ratio of various DNA sequences. Values of 0.5 or more were determined as the BRCA1-like Type (BRCAness) and those of less than 0.5 as the Sporadic Type to analyze pathological complete response (pCR) rate, recurrence, and survival. pCR (ypT0/Tis/N0) was observed in 15 patients (pCR rate: 37.5%). These patients had no recurrence. Twelve patients recurred, 8 died from breast cancer. The BRCA1-like Type were 22 and Sporadic Type were 18 in CNB specimens. No major differences were observed between the BRCA1-like Type and Sporadic Type with pCR rate, recurrence rate and survival. Twenty four surgical specimens of non-pCR patients were available and 9 were BRCA1-like Type, who had more recurrences (7/9 vs. 5/15), and their relapse-free survival was also lower (p<0.05) than that of Sporadic Type. Seven BRCA1-like Type patients remained BRCA1-like Type in surgical specimens, were worse in recurrence (p<0.01) and survival (p<0.05) compared with 6 patients whose BRCA status in surgical specimens turned to Sporadic Type. New clinical trials assessing the true recurrence (TR) rate of BRCA-type patients are expected since neither platinum-containing drugs nor poly (ADP-ribose) polymerase (PARP) inhibitors are effective against tumors with nonfunctional BRCA genes.